Bunyamwera Bunyavirus Nonstructural Protein NSs Counteracts the Induction of Alpha/Beta Interferon - Weber, Friedemann (American Society for Microbiology, 2002)
Production of alpha/beta interferons (IFN-α/β) in response to viral infection is one of the main defense mechanisms of the innate immune system. Many viruses therefore encode factors that subvert the IFN system to enhance their virulence. Bunyamwera virus (BUN) is the prototype of the Bunyaviridae family. By using reverse genetics, we previously produced a recombinant virus lacking the nonstructural protein NSs (BUNdelNSs) and showed that NSs is a nonessential gene product that contributes to viral pathogenesis. Here we demonstrate that BUNdelNSs is a strong inducer of IFN-α/β, whereas in cells infected with the wild-type counterpart expressing NSs (wild-type BUN), neither IFN nor IFN mRNA could be detected. IFN induction by BUNdelNSs correlated with activation of NF-κB and was dependent on virally produced double-stranded RNA and on the IFN transcription factor IRF-3. Furthermore, both in cultured cells and in mice lacking a functional IFN-α/β system, BUNdelNSs replicated to wild-type BUN levels, whereas in IFN-competent systems, wild-type BUN grew more efficiently. These results suggest that BUN NSs is an IFN induction antagonist that blocks the transcriptional activation of IFN-α/β in order to increase the virulence of Bunyamwera virus.